GEN-9 WHOLE GENOME SEQUENCING ANALYSIS REVEALS STRUCTURAL VARIANTS CONTRIBUTE TO TUMOR EVOLUTION IN IDH-MUTANT GLIOMA. (3rd December 2022) - Funakoshi, Yusuke; Nakashima, Takuma; Uneda, Atsuhito; Nambu, Shohei; Tanaka, Shota; Ishida, Joji; Saito, Ryuta; Hanaya, Ryosuke; Yoshimoto, Koji; Narita, Yoshitaka; Suzuki, Hiromichi
Abstract: Introduction: Recent large-scale sequencing projects for IDH-mutant adult-type diffuse glioma (Astrocytoma, IDH-mutant and Oligodendroglioma, IDH-mutant and 1p/19q-codeleted) have revealed the genetic landscape of coding mutations. However, little is yet known about the non-coding regions and structural variants (SVs). We analyzed deep (> x120) whole-genome sequencing (WGS) to delineate the comprehensive genetic lesions of IDH-mutant gliomas. Methods: We investigated WGS of 228 cases with IDH-mutant glioma (204 cases in our cohort along with 24 publically available cases). Results: The median tumor mutational burden in astrocytoma and oligodendroglioma was 2.0/Mb and 1.7/Mb, respectively. The median number of SV per case was 15.0 and 4.5, respectively. SV was involved in known driver genes in 7.7% of cases, supporting a model in which accumulation of SV as well as mutation drives tumor initiation and/or progression. The distribution of SV is biased on each chromosome, suggesting that each chromosome has a distinct susceptibility for SV. In IDH-mutant astrocytoma, complex SVs are significantly enriched on chromosome 12 which frequently involves CDK4, suggesting that SVs could lead to tumor evolution. The numbers of SVs and single nucleotide variants (SNVs) per case are correlated, presuming that IDH-mutant glioma can progress by acquiring both SNV and SV in a time-dependent manner. Conclusion: SV could contribute to the development of IDH-mutant gliomas as well as mutations. Since WGS has a great resolution for genetic alterations, further analysis would enable us to uncover glioma pathogenesis.